2020
DOI: 10.1002/ccd.28712
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function testing guided antiplatelet therapy reduces cardiovascular events in Chinese patients with ST‐segment elevation myocardial infarction undergoing percutaneous coronary intervention: The PATROL study

Abstract: Background Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor inhibitor has become the standard of care to reduce thrombotic events in patients with acute coronary syndrome or after percutaneous coronary intervention (PCI). The role of routine platelet function testing (PFT) in patients treated with DAPT after PCI remains controversial and evidence of PFT‐guided antiplatelet therapy for patients with ST‐segment elevation myocardial infarction (STEMI) undergoing primary PCI is limited. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
0
21
1
Order By: Relevance
“…However, the INR remains controversial. Despite lower INR target of 1.5-2.0 recommended for triple anti-thrombotic therapy by previous studies (24), the risk of hemorrhagic complication was still higher in the LVA group in the current study (6.67% vs. 2.40%, P<0.01). Further randomized controlled trials about antithrombotic therapy strategy including novel oral anticoagulants are required to balance the risk of embolism and bleeding.…”
Section: Prognosis Of Lva In the Contemporary Pci Eracontrasting
confidence: 77%
“…However, the INR remains controversial. Despite lower INR target of 1.5-2.0 recommended for triple anti-thrombotic therapy by previous studies (24), the risk of hemorrhagic complication was still higher in the LVA group in the current study (6.67% vs. 2.40%, P<0.01). Further randomized controlled trials about antithrombotic therapy strategy including novel oral anticoagulants are required to balance the risk of embolism and bleeding.…”
Section: Prognosis Of Lva In the Contemporary Pci Eracontrasting
confidence: 77%
“…Sensitivity meta-analyses show that the results regarding all-cause mortality, CV mortality, and MI had limited robustness, whereas the results regarding stent thrombosis were more robust (Table 2). Funnel plots revealed outlier populations (see Figure S4 , Supplemental Digital Content 1 , http://links.lww.com/JCVP/A777), all with considerably higher event rates in the comparison group (ticagrelor) than other RCTs (>10%: all-cause mortality, CV mortality, and MI 26,48 and >4%: stent thrombosis 41 ). In our most restricted sensitivity meta-analyses, focusing on RCTs without zero-event arms, without major risk of bias, recruiting patients after the PLATO trial, with 6–12 month follow-up, and not representing outlier populations, there was no difference between clopidogrel and ticagrelor regarding all-cause mortality (I 2 : 0%), CV mortality (I 2 : 15%), and MI (I 2 : 0%), the pooled RD estimate being very close to 0.…”
Section: Resultsmentioning
confidence: 99%
“…11,24,27,29 Regarding major bleeding, our finding of an increased risk for ticagrelor diverges from results in the PLATO trial where no significant difference was found. 6 However, the compiled results may not be too surprising because the risk of bleeding increases by age, 18 and the studied population in 8 of 13 RCTs contributing events to the meta-analysis without zero-event trials had a higher mean/ median age than in the PLATO trial, 11,23,24,26,29,33,37,48 where the median age was 62 years. 6 The increased bleeding risk by age is also illustrated by the low rate (5%) of clinically significant bleeding in the ticagrelor group in Berwanger et al 27 with a median age of 59 years, whereas Gimbel et al, 11 with a median age of 77 years, reported that such bleedings occurred in 24%.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to genotype testing, platelet function testing is more manageable and cost-effective, providing quick results determining responses to antiplatelet therapy in real-time [ 31 ]. It was observed in the PATROL study that for patients with HPR, identified by platelet function testing, switching clopidogrel to ticagrelor could significantly improve 1-year clinical outcomes without increasing the risk of bleeding [ 32 ]. However, platelet function testing has certain limitations given that it requires patients to be on treatment to define responsiveness [ 31 ].…”
Section: Discussionmentioning
confidence: 99%